Do ethnicity and sex matter in pay? analyses of 8 ethnic groups in the Dutch labour market - Zorlu, Aslan (2003)
Using the CBS-micro survey, ethnic and gender wage differentials in the Netherlands are examined between native Dutch labourers and 7 ethnic minority groups that are highly differentiated in their human capital endowment and immigration history. Estimations indicate that wage discrimination occurs mainly on the basis of their ethnic background rather than gender. Moroccans suffer the largest wage gap due to discrimination. This result is likely an indication of employer’s response on the deteroriating image of Moroccans in the Netherlands in recent years. Also, Eastern-European and non-European workers that are composed by more refugees and other recent immigrants are disfavoured, so are Caribbean and Indonesian men. Immigrants from the EU-countries rarely face wage discrimination.